Prospective analysis of type I thyroplasty using gore-tex implant - Mohanty, Sanjeev; ., Sreenivas; T., Vinay Raj; ., Devipriya; M., Vinoth (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Vocal cord paralysis is a clinical sign caused by paralysis of intrinsic muscles of larynx due to dysfunction of recurrent laryngeal nerve. There are several methods available surgically for the medialisation of the abducted vocal cord. One of the common effective modality is the Gore-Tex medialisation thyroplasty. The results depend on a number of factors including the surgical expertise and extrusion of the Gore –Tex implant. This study is aimed at analysis of all Gore-Tex medialisation thyroplasty done at our centre. Prospectively asses and analyze the vocal outcomes and quality of life of patients in type 1 medialisation thyroplasty using Gore-Tex implant. Methods: Prospective study of 48 months on 30 patients with unilateral vocal cord paralysis. Surgical procedure for the patients was standardized by using Gore-Tex implant to medialize the cord. Video-Laryngoscopy at end of 1st month and stroboscopy & voice analysis at end of 3rd month post treatment, the parameters used for the pre and post treatment objective analysis are a) stroboscopic analysis, b) psychoacoustic evaluation, c) maximum phonation time, d) patient’s self-assessment. Results: In our study of 30 patients with a follow up period of 48 months, we can conclude as follows – a)unilateral vocal cord paralysis does not have age or gender specificity, b)statistically significant vocal cord palsy affects the left side more by 70%, c)post op Gore-tex medialisation thyroplasty showed a statistically highly significant improvement in psychoacoustic, mean phonation time, d)post op Gore-Tex medialisation thyroplasty showed a statistically significant improvement in videostroboscopic analysis. Conclusions: Psycho acoustic, mean phonation time analysis would complement each other in the assessment of the medialisation thyroplasty thus obviating videostroboscopy.